Formation of Income of Enterprises Sufficient for Self-Financing - Rakhmat Musaev (Research Parks Publishers, 2022)
The article deals with the modification of the category of production costs. Two diametrically opposed concepts are also considered on the cardinal issues of forming the cost of production. Particular attention is paid to the role of the wage fund in the sulfur of new distribution relations that are emerging in connection with the transition of enterprises to a new model of self-financing.